A Note on Liquid Fertilizer from Shrimp and Fish Wastes - Ismail, P. K.; Madhavan, P. (Fishery Technology, 1970)
The rapid increase in the volume of export trade in canned and frozen prawns over a decade presents now the problem of disposal of very huge quantity of head and shell wastes. Presently a small portion of it is converted into meal by drying and powdering, the rest being either thrown away or in limited cases, used as manure. Decaying proteins and other odour-producing materials in shrimp waste cause stinking smell unless it is processed immediately. Modern trends in agricultural practice are to use fertil1zers of particular NPK ratios for particular crops and hence the use of shrimp waste or fish waste alone as a manure is not satisfactory. The present note reports a simple method of preparation of liquid fertilizer of two different NPK ratios suitable for common crops of Kerala like coconut, arecanut, ginger tapioca, pepper and vegetables. The process is characterised by the simplicity of the procedure and the low cost of the raw materials involved.